Financial crisis and persistence: evidence from sticky expectations consumption growth model. Issue 17 (9th April 2019) - Kumar, Saten; Jia, Pengfei
ABSTRACT: We estimate the degree of stickiness in aggregate consumption growth for the U.S. considering the effects of the Great Recession. The behavior of stickiness estimate in the crisis is somewhat as the U-shaped pattern. Our findings imply that during the crisis consumers' attentiveness to aggregate information has slightly increased, thereby reducing the persistence of aggregate consumption growth. However, the reduction in persistence is transitory. Since 1980, the U.S. faced five recessions and in most of them the degree of stickiness declined, albeit temporarily.